Assessment of maternal cerebral blood flow velocity by transcranial Doppler ultrasound before delivery and in the early postpartum period. (16th February 2019) - Batur Caglayan, Hale Z.; Nazliel, Bijen; Cinar, Mehmet; Ataoglu, Esra; Moraloglu, Ozlem; Irkec, Ceyla
Abstract: Objective: This prospective observational study aimed to identify the effects of labor on cerebral hemodynamics by measuring the middle cerebral artery (MCA) blood flow velocity by transcranial Doppler ultrasound (TCD), and the related factors just before delivery and within the 24 h after delivery. Methods: The study included 35 healthy pregnant women with a gestational age of >37 weeks who were in labor and a control group including healthy, age-matched, nonpregnant women ( n  = 24). Demographic characteristics and significant clinical information of pregnant women were recorded. The MCA blood flow velocity was assessed by TCD just before and within 24 h after delivery. The parameters assessed by TCD were mean cerebral blood flow velocity (MCBFV), peak systolic velocity (PSV), pulsatility index (PI), resistance index (RI), and systolic/diastolic ratio. Results: There was no significant difference between the pregnant and nonpregnant women regarding age (27 ± 5 years versus 28 ± 7 years; p  = .751). The MCBFV, PSV, PI, and RI showed a significant increase within the 24 h after delivery as compared with those before delivery. Comparison of the pregnant women with the control group in terms of the values of all parameters related to the MCA blood flow velocity revealed that the values that were significantly low before delivery reached to the level of the control group after delivery Conclusion: The findings of this study demonstrated that the blood flow velocity of the MCA decreased during the late pregnancy period and increased in the early postpartum period to the level similar to that of the nonpregnant group.